The Use of Infocus to Improve Student Learning Activities in Class X Senior High School of SMAS YPST Porame - Hijrawati; Juraid; Ika Nur Jayanti (Kirana Publisher (KNPub), 2026)
This study aims to analyze the use of infocus technology in improving student learning activities in history lessons in grade X SMAS YPST Porame. The study used a qualitative approach with a field research design carried out in a natural setting. The research subjects consisted of seven grade X students selected using a purposive sampling technique based on the criteria of active involvement in history learning and technology-based learning experiences. Data collection was carried out through observation, semi-structured interviews, literature studies, and documentation. Data were analyzed using an interactive analysis model that includes data reduction, data presentation, and drawing conclusions. The results showed that the use of infocus had a positive impact on improving student learning activities, both in cognitive, affective, and social aspects. Visual media in the form of images, videos, and historical maps helped students understand the material more concretely, increased learning interest, and encouraged student activeness in discussions and group work. However, this study also found several obstacles in the use of infocus, such as technical constraints, limited number of devices, classroom conditions, and teacher preparation time. These obstacles were overcome through teacher adaptive strategies, including preparing alternative learning methods, involving students in preparing tools, and making adjustments during the learning process. This study concludes that the planned and creative use of infocus can improve the quality of history learning, even in conditions of limited facilities.